Dry Eye Epidemiology in Patients before Refractive Operations - S. N. Sakhnov; S. V. Yanchenko; A. V. Malyshev; Y. A. Kalantaevskaya; R. A. Ismaylova; E. M. Ehieva; M. V. Grishenko; I. V. Gorbunova; O. F. Ozhug; O. A. Klokova (Oftalʹmologiâ, 2018)
Purpose. To evaluate the prevalence, clinical severity, clinical and pathogenetic variants and etiology of dry eye (DE) in patientsbefore refractive surgery. Methods. OSDI testing, lipid interferential test, TBUT, Shirmer-1, -2 tests, compression Norn test in Korbmodification, calculation of xerosis index by Bijsterveld, tear meniscus index evaluation, LIPCOF test, evaluation of epitheliopaty and microerosion by Tseng and lid viper epitheliopaty were performed in 600 myopia (with or without astigmatism) patients (234 men, 366 women; 30.1 ± 6.26 years old) before refractive surgery. The structure of the DE etiological conditions, was studied both in DE patients and non-DE subjects with calculation of the Pearson xi-square test. To estimate the strength of the connection between the etiological condition and the DE, the normalized value of the Pearson coefficient (C') was used. Results. The dry eye prevalence was 38.83% (of them, 71.76% was mild, 28.83% — moderate, by Brzhesky). Clinical and pathogenetic variants of mild DE included: lipid deficiency (53.29%); lipid-mucin deficiency (26.95%); mucin deficiency (11.38%); state without signs of lipid or mucin deficiency (8.38%). In patients with moderate DE were identified: isolated aqueous deficiency (6.06%); aqueous-lipid deficiency (34.85%); aqueous-mucin deficiency (7.58%); aqueous-lipid-mucin deficiency (51.52%). Statistically significant (р < 0.01) etiological conditions for the disease in patients with diagnosed DE include: contact lenses wearing (C' = 0.349); visual display use (C' = 0.342); the use of medication affecting tear production or tear film stability (C' = 0.41); application of cosmetics (cosmetic pencil or mascara) in the intercostal space of the eyelid margin — in the area of the excretory ducts of the meibomian glands (C' = 0.44); meibomian glands dysfunction (C' = 0.782); chronic allergic conjunctivitis (C' = 0.543); the presence of gynecological pathology (C' = 0.413); thyroid gland diseases (C' = 0.32); allergy (C' = 0.563); female sex (C' = 0.559). Conclusion: Raising the awareness of ophthalmologists about the prevalence of early DE manifestations in patients before refractive surgery will help optimize the detection of this pathology. The obtained data on the structure of DE clinical and pathogenetic variants and the etiological prerequisites can serve as a basis for the development of therapy. One of the most prevalence and significant etiological condition for DE was MGD, leading to lipid-deficiency, which determines the direction of etio-pathogenetic treatment — the eyelids hygiene.